2021 IT trends in higher education to watch - Abdul Manaf, Suhaily Maizan; Wan Musa, Wan Mardiana; Mohd Said, Nur Shafini; Adenan, Nur Dalila; Omar Ali, Siti Rapidah (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2021)
In several ways, technology has revolutionised the future of education. With the transition to online learning and the growing emphasis on technology to ensure students' health and safety, technology adoption in higher education is rapidly increasing